2023
DOI: 10.1177/10963480231151674
|View full text |Cite
|
Sign up to set email alerts
|

The Greener, the Better? Probing Green Innovation in Pilgrimage Tourism Destinations

Abstract: This study examines the importance of pilgrimage tourism to green innovation and assesses the factors that influence pilgrimage tourism efforts and implementation to ensure green innovation. The results of semi-structured, in-depth interviews with religious figures and pilgrims, supplemented by secondary sources, show that linking pilgrimage capabilities and religious organizations is critical to sustaining green innovation rather than focusing on the dispersed state of consciousness. The findings underscore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…The authors found that cognitive linguistics can be effectively utilized to develop impactful sustainability communication strategies, emphasizing the importance of linguistic framing in promoting responsible practices. Senbeto (2023) explored green innovation in pilgrimage tourism destinations and its impact on sustainability and tourist satisfaction. The study revealed that green innovation enhances the sustainability of pilgrimage destinations and improves tourist satisfaction, emphasizing the potential benefits of integrating sustainability practices in religious tourism.…”
mentioning
confidence: 99%
“…The authors found that cognitive linguistics can be effectively utilized to develop impactful sustainability communication strategies, emphasizing the importance of linguistic framing in promoting responsible practices. Senbeto (2023) explored green innovation in pilgrimage tourism destinations and its impact on sustainability and tourist satisfaction. The study revealed that green innovation enhances the sustainability of pilgrimage destinations and improves tourist satisfaction, emphasizing the potential benefits of integrating sustainability practices in religious tourism.…”
mentioning
confidence: 99%